Processing Distracting Non-face Emotional Images: No Evidence of an Age-Related Positivity Effect - Madill, Mark; Murray, Janice E. (Frontiers in Psychology, 2017)
Cognitive aging may be accompanied by increased prioritization of social and emotional goals that enhance positive experiences and emotional states. The socioemotional selectivity theory suggests this may be achieved by giving preference to positive information and avoiding or suppressing negative information. Although there is some evidence of a positivity bias in controlled attention tasks, it remains unclear whether a positivity bias extends to the processing of affective stimuli presented outside focused attention. In two experiments we investigated age-related differences in the effects of to-be-ignored non-face affective images on target processing. In Experiment 1, 27 older (64-90 years) and 25 young adults (19-29 years) made speeded valence judgments about centrally presented positive or negative target images taken from the International Affective Picture System. To-be-ignored distractor images were presented above and below the target image and were either positive, negative or neutral in valence. The distractors were considered task relevant because they shared emotional charactertistics with the target stimuli. Both older and young adults responded slower to targets when distractor valence was incongruent with target valence relative to when distractors were neutral. Older adults responded faster to positive than to negative targets did not show increased interference effects from positive distractors. In Experiment 2, affective distractors were task irrelevant as the target was a three-digit array and did not share emotional characteristics with the distractors. Twenty-six older (63-84 years) and 30 young adults (18-30 years) gave speeded responses on a digit disparity task while ignoring the affective distractors positioned in the periphery. Task performance in either age group was not influenced by the task-irrelevant affective images. In keeping with the socioemotional selectivity theory, these findings suggest that older adults preferentially process task-relevant positive non-face images but only when presented within the main focus of attention.